Ambush marketing in sport – characteristics of combating the phenomenon - Rzeszowski, Jakub (Journal of Education, Health and Sport, 2018)
In the article, the author has characterized the phenomenon of ambush marketing by describing its immense diversity. Reasons and the practical status of this phenomenon have also been indicated. Subsequently, attention has been drawn to provisions of the Polish law that may turn out helpful, but insufficient, when it comes to combating practices of ambush marketing. In the summary, the author states that the Polish law system still hasn’t decided to pass a special act to regulate this issue despite some past opportunities to do so.